2015
DOI: 10.3109/10717544.2015.1122674
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and efficacy of thermosensitive liposomes containing paclitaxel

Abstract: To increase the anti-tumor activity of paclitaxel (PTX), novel temperature-sensitive liposomes loading paclitaxel (PTX-TSL) were developed. In vitro, characteristics of PTX-TSL were evaluated. The mean particle diameter was about 100 nm, and the entrapment efficiency was larger than 95%. The phase-transition temperature of PTX-TSL determined by differential scanning calorimetry was about 42C. The result of in vitro drug release from PTX-TSL illustrated that release rate at 37 C was obviously lower than that at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 32 publications
2
22
0
1
Order By: Relevance
“…Wang and coworkers reported more PTX release at 42°C than at 37°C. An in vivo study of a xenograft lung tumor model showed enhanced drug release in tumor tissues when hyperthermia occurred, resulting in increased tumor growth suppression, compared with nontemperature-sensitive liposome and free drug treatment (Wang, Zhang, et al, 2016). …”
Section: Stimuli-responsive Drug Deliverymentioning
confidence: 99%
“…Wang and coworkers reported more PTX release at 42°C than at 37°C. An in vivo study of a xenograft lung tumor model showed enhanced drug release in tumor tissues when hyperthermia occurred, resulting in increased tumor growth suppression, compared with nontemperature-sensitive liposome and free drug treatment (Wang, Zhang, et al, 2016). …”
Section: Stimuli-responsive Drug Deliverymentioning
confidence: 99%
“…Iron oxide-based magnetic nanoparticles are extensively investigated in nanomedicine for their biocompatibility, their contrast agent properties, and their ability to generate heat when submitted to an alternating magnetic field [80,81]. Wang et al designed a multiple magnetic hyperthermia-mediated release system for combination therapy using an injectable, biodegradable, and thermosensitive polymeric hydrogel [82]. Wang et al noted that the therapeutic effect of the combination therapy in vivo significantly reduced the tumors and was dependent on the number of cycles of hyperthermia [82].…”
Section: Core-shell Nanoparticlesmentioning
confidence: 99%
“…Wang et al designed a multiple magnetic hyperthermia-mediated release system for combination therapy using an injectable, biodegradable, and thermosensitive polymeric hydrogel [82]. Wang et al noted that the therapeutic effect of the combination therapy in vivo significantly reduced the tumors and was dependent on the number of cycles of hyperthermia [82].…”
Section: Core-shell Nanoparticlesmentioning
confidence: 99%
“…Apart from anthracyclines [65], the drugs bleomycin [55], melphalan [56], placitaxel [57], docetaxel [58], and gemcitabine [59] have been encapsulated into TSL and delivered to tumors, while reducing systemic drug toxicities.…”
Section: Payloadsmentioning
confidence: 99%